2018
DOI: 10.1039/c8nr01266k
|View full text |Cite
|
Sign up to set email alerts
|

Monodisperse and brightly luminescent CsPbBr3/Cs4PbBr6 perovskite composite nanocrystals

Abstract: The microscale composite structure strategy of embedding CsPbBr3 nanocrystals (NCs) in the microscale Cs4PbBr6 matrix (CPB113/CPB416) has successfully demonstrated its ability to resolve the fluorescence quenching of perovskite NCs in the solid agglomeration state due to the loss of quantum confinement. Unfortunately, the controllable synthesis of monodisperse nanoscale composites with bright emission in the solid state remains a great challenge. Here, we present for the first time a novel supersaturated recry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
81
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 105 publications
(86 citation statements)
references
References 35 publications
4
81
0
1
Order By: Relevance
“…As aforementioned, the inorganic passivation shell of Cs 4 PbBr 6 crystals might be a good way to help radiative processes outpace with Auger transition. Moreover, the synthetic condition of Cs 4 PbBr 6 crystals is compatible with that of CsPbBr 3 NPLs …”
Section: Exciton Behavior Of Nanoplateletsmentioning
confidence: 88%
See 4 more Smart Citations
“…As aforementioned, the inorganic passivation shell of Cs 4 PbBr 6 crystals might be a good way to help radiative processes outpace with Auger transition. Moreover, the synthetic condition of Cs 4 PbBr 6 crystals is compatible with that of CsPbBr 3 NPLs …”
Section: Exciton Behavior Of Nanoplateletsmentioning
confidence: 88%
“…[70] Xuan et al reported a new fashion to decrease the crystal grains down to tens of nanometer sizes by introducing 2-methylimidazole (MeIm) as the capping ligand to regulate their growth rate (Figure 11g). [71] Apart from dissolving the halide salts, MeIm combined with precursor stirring time played a key role in morphology and size. The addition of MeIm not only controls the parameters (the composition rate, the size, and dispersity) of CsPbBr 3 in the composite nanocrystals, but can also help controllably obtain the monodispersed and hexagonal Cs 4 PbBr 6 matrix.…”
Section: Wwwadvancedsciencenewscom Wwwsmall-methodscommentioning
confidence: 99%
See 3 more Smart Citations